2019
DOI: 10.1002/gps.5182
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and economic burden among caregivers of patients with Alzheimer's disease in Canada

Abstract: Objective To estimate the clinical and direct medical economic burden among Alzheimer disease (AD) caregivers using real‐world, longitudinal patient‐level data in Canada. Methods/Design This retrospective observational study assessed the clinical and direct medical economic burden among individuals who cohabitate with AD patients (“AD caregiver cohort”) compared with older adults who were cohabiting with another adult without dementia (“comparison cohort”) using real‐world data from the Southwestern Ontario da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
6
1
Order By: Relevance
“…Similar to findings of a recent systematic review of the burden and health impacts among DS caregivers, we found that most data on caregiving burden are qualitatively-and self-reported [78], with no clinician-assessed studies of caregiver health impacts identified. Studies in other therapeutic areas have demonstrated that caregiver health is negatively affected by caregiving demands [115,116] and studies to characterize this more accurately would be of value in DS.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to findings of a recent systematic review of the burden and health impacts among DS caregivers, we found that most data on caregiving burden are qualitatively-and self-reported [78], with no clinician-assessed studies of caregiver health impacts identified. Studies in other therapeutic areas have demonstrated that caregiver health is negatively affected by caregiving demands [115,116] and studies to characterize this more accurately would be of value in DS.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-seven reported data from Asia [27, 34, 35, 49, 51, 52, 54, 56-59, 63, 65, 67, 73, 83-87, 98, 99, 104, 109, 112, 113, 125, 142, 143, 146, 156, 157, 159, 164, 165, 170]. Thirty-two studies reported data from the US [29, 32, 33, 42, 45, 46, 53, 60, 62, 71, 72, 91-94, 97, 101, 103, 106, 114, 124, 127, 139, 141, 145, 148, 149, 152, 161, 163, 167, 174], and four studies reported data from Canada [30,44,140,158]. Fewer studies reported data from Australia (two [37,61]) and South America (eight [38,40,55,64,76,77,160,173]).…”
Section: Data Sources and Study Characteristicsmentioning
confidence: 99%
“…16,17 Caregivers at lower educational levels are more likely to experience burden, as the risk of developing stress symptoms is likely to be higher. 17,18 Working status It has been seen that caregivers have had to quit their jobs or reduce the time they devote to their work to a great extent because of their caregiving responsibilities. It is stated that while working caregivers are trying to maintain not only business life but also family life, they have to do the third shift for the patient and they cannot allocate enough time for themselves.…”
Section: Education Statusmentioning
confidence: 99%